PENINGKATAN KEMAMPUAN PEMBUKTIAN DAN KEMANDIRIAN BELAJAR MATEMATIK MAHASISWA MELALUI PENDEKATAN M-APOS - YERIZON (2011)
Some studies reported that many students faced serious difficulties on constructing mathematical proof. A post test control group design experiment was conducted to improve students' mathematical proving abilities by using modified APOS (M-APOS) teaching method. The study involved 124 students of Real Analysis classes of a state university in Padang. Instruments of the study were: a proof ability test, and a Likert model self regulated learning scale. The data were analyzed by using two path ANOVA. The study found that: 1) attainment and gain on students' reading proof ability and students' proving ability of modified APOS class were classified as mediocre and better than students' abilities of conventional class which classified as low; 2) students' self regulated learning of M-APOS class was better than students' self regulated learning of conventional class, and both of them were classified as medium. However ther was no difference between students' gain on self regulated learning of both classess and they were classified as very low. There were not interaction between learning approach and department (mathematics and mathematics education) and between learning approach and mathematics prior knowledge on proof reading and proof construction abilities. There was association between proof reading ability and proof construction ability.